Identification and Analysis of Project Management Success Factors in Information Technology SMEs (2018)
This article identifies and analyses the success factors involved in project management through an exploratory study that encompasses nineteen interviews, fifty-seven surveys and one session with a focus group of project managers, department managers who have taken the role of project managers and general managers of small and medium-sized enterprises (SMEs) of the information technology (IT) sector in Bogota, Colombia. After analyzing the information, the authors identified eleven factors for the achievement of project management goals in these organizations. These comprise managerial, organizational and sector aspects that influence the resource management and leadership in projects of SMEs of information technology.